The effect of quality of food source on macadamia nut damage by Gymnandrosoma aurantianum (Lepidoptera: Tortricidae) - Blanco-Metzler, Helga (2013)
The effect of nitrogen content, the secondary compounds (tannin and proanthocyanidin) content, the dry matter content of 4 clones, and the different developmental stages of macadamia nuts, on the abundance of Gymnandrosoma aurantianum, was studied. Nitrogen content differed between clones and the stages of development of the nuts, being highest in the most tolerant clones 508>660>344>246. Highest dry matter contents were found in the tolerant clones, 508 and 660, and in the outer layer, than in the susceptible clones 246 and 344 and in the inner layers (2 and 3). Proanthocyanidin content was highest in layer 2 of clones 508 and 660 than in clones 246 and 344. Results show that food quality affects the performance of nutborer larvae, where the larvae have to overcome first a physical barrier, followed by a chemical barrier, to be able to feed on macadamia nuts.